Theatre Education at Reduta - Wanda Świątkowska (Pamiętnik Teatralny, 2020)
The article presents the history and principles of theatre education at Reduta in its successive forms: from Koło Adeptów [The Apprentice Circle], established in 1921, through the Reduta Institute, to Okop [The Trench], which was the last pre-war incarnation of the school. Based on documents and memoirs, the article discusses Reduta’s comprehensive and holistic model of education, in which regular theoretical classes were accompanied by practical and physical exercises. A crucial part of the education process was student participation in the theatre’s daily operations: rehearsals, preparation of stage productions, and tours. The aim of the school was to offer future artists comprehensive preparation for various theatre functions, as well as to produce ideologically engaged social activists, who consider serving the society through art as their primary task and mission. A comparison between Reduta’s schools and other educational initiatives confirms that in terms of scope, curriculum, work methods, practices, as well as atmosphere, the former were indeed pioneering and stood out from traditional pre-war drama teaching. Published as an appendix to the article is its source material: Juliusz Osterwa, Okop, edited and with an introduction by the author of the article.